2008
DOI: 10.1002/anie.200705012
|View full text |Cite
|
Sign up to set email alerts
|

Ditryptophan Conjugation Triggers Conversion of Biotin Fibers into Soft Spherical Structures

Abstract: Trigger happy: Biotin and its methyl ester form long fibers in solution, which are transformed into soft spherical structures upon simple conjugation with ditryptophan dipeptide (see picture). Such morphogenesis is not achieved in a controlled fashion by other aromatic amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 22 publications
0
53
0
Order By: Relevance
“…Ga + ions were used to mill these soft structures and SEM micrographs revealed that these structures are hollow from inside ( Fig. 8) [40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ga + ions were used to mill these soft structures and SEM micrographs revealed that these structures are hollow from inside ( Fig. 8) [40].…”
Section: Resultsmentioning
confidence: 99%
“…The sample was directly mounted on the stage under native conditions and images were taken with the help of focused-ion-beam/scanning electron microscope dual beam system (NOVA 600 NANOLAB, D97 FEI). The milling process of soft material depends upon three important things viz beam current, accelerating voltage and mill depth to minimize surface artifacts [40].…”
Section: Focused Ion Beam-scanning Electron Microscopy (Fib-sem)mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of our investigations, we have discovered peptide-based supramolecular ensembles where some of them respond to colchicine, physiologically relevant cations, and covalently attached structure modifiers [12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%